Analisis Pengaruh Transmisi Kebijakan Moneter Melalui Jalur Suku Bunga Dan Harga Aset Terhadap Inflasi Di Indonesia Tahun 2017-2023 - Aditya, I Made Oka; Chaidir, Taufiq; Arini, Gusti Ayu (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to analyze the effect of monetary policy transmission through the interest rate channel using the Bank Indonesia Certificate Interest Rate (RSBI) and the Interbank Money Market Interest Rate (RPUAB) indicators and through the asset price channel using the Composite Stock Price Index (CSPI) and Real Investment (IR) indicators. The data used is secondary data obtained from the official website of Bank Indonesia (BI) and the Central Bureau of Statistics (BPS). The data analysis used is the Vector Error Correction Model (VECM) with the Eviews 10 application. The results of this study indicate that in the long run the Bank Indonesia Certificate Interest Rate (RSBI) has a significant negative effect on inflation, the Interbank Money Market Interest Rate (RPUAB) has a significant positive effect on inflation, the Composite Stock Price Index (CSPI) has a significant negative effect on inflation, and Real Investment (IR) has a positive and significant effect on inflation. While in the short term, the Bank Indonesia Certificate Interest Rate (RSBI) has a negative and insignificant effect on inflation, the Interbank Money Market Interest Rate (RPUAB) has a negative and insignificant effect on inflation, the Composite Stock Price Index (CSPI) has a negative and insignificant effect on inflation, and Real Investment (IR) has a positive and insignificant effect on inflation.